Correction: Methotrexate-conjugated mPEG–PCL copolymers: a novel approach for dual triggered drug delivery. (17th June 2019) - Rostamizadeh, Kobra; Manafi, Mostafa; Nosrati, Hamed; Manjili, Hamidreza Kheiri; Danafar, Hossein
Abstract : Correction for 'Methotrexate-conjugated mPEG–PCL copolymers: a novel approach for dual triggered drug delivery' by Kobra Rostamizadeh et al., New J. Chem., 2018, 42, 5937–5945.